Metallogeny in the Bangong–Nujiang belt, central Tibet, China: A review - Song, Yang; Tang, Juxing; Lin, Bin; Yang, Chao; Sun, Hao (Frontiers in Earth Science, 2023)
The Bangong-Nujiang metallogenic belt consists of scattered Tethyan oceanic blocks, mainly distributed underneath the margins of Qiangtang and Lhasa terranes in central Tibet. A sketch of a new world-class metallogenic belt has been reported in this region recently, based on the geological mapping and ore deposit prospecting over the last two decades. It currently comprises inferred resources of 30 Mt Cu, and 500 t Au, together with several Cr-Ni, Fe, and W (Mo) resources, forming a significant potential area for future mineral exploration. These metals are mainly hosted in porphyry copper, skarn copper, skarn iron, orogenic gold, quartz vein tungsten, and ophitic chromite deposits. The mineral deposits in the BNMB have been widely recognized in different localities, including the southern edge of the southern Qiangtang block, part of the north Lhasa block, and even part of the central Lhasa block, indicating they were formed in variable geological settings, from open, subduction and collision to the extension of the Bangong-Nujiang ocean. Specifically, five major tectonic events contributed to mineralization, including the stage 1 (240-165 Ma) initial opening of the Bangong-Nujiang ocean, stage 2 (165-145 Ma) oceanic subduction, stage 3 (145-100 Ma) close of the ocean, stage 4 (100-65 Ma) continent-continent collisional orogenesis, and stage 5 (65-0 Ma) post-orogenesis. At stage 1, Cr-Ni deposits were formed during the initial opening of the ocean; porphyry-epithermal Cu (Au), skarn Fe, and minor orogenic Au deposits were formed at stage 2 and stage 3; a younger pulse of a few porphyry-skarn Cu±Mo and orogenic Au deposits were formed during stage 4; finally, W(Mo) deposits were generated at stage 5. In general, porphyry Cu systems, orogenic Au, and skarn Cu polymetallic deposits that occurred in the subduction and post-collisional settings (<100 Ma) W(Mo) are the most potential deposit types for future exploration. An in-depth investigation of several scientific problems, such as addressing the tectonic setting, magmatism, and metallogeny of this region, and genetic linkage of these deposit preservations to plateau uplift, is essential for the future success of exploration in the Bangong-Nujiang metallogenic belt.